Relación entre estrés laboral y engagement laboral en colaboradores - Camilla Paola Cisneros Diaz (2024)
Within the work environment there are several stressors that influence the employee's work engagement. These are caused by the work demands presented by the employee in this environment, being perceived as a habitual aspect; however, they can even lead to an impact on their personal well-being if they are not able to regulate them. The objective of this study is to identify the relationship between work stress and work engagement in employees. A applied investigation was carried out taking into account the methodological recommendations of the PRISMA guide. The search for information on the ten articles was carried out using the SCOPUS, Ebsco, Proquest and APA PsycNET databases. As a result, it was found that most of the research related both variables negatively. It was concluded that the level of work engagement will depend on the type of stressor, the employee's assessment of it and the mediating variables present in the work environment.